Initial Evaluation of Pain Intensity Among Depressed Patients as a Possible Mediator Between Depression and Pain Complaints - Nitzan, Uri; Hecht, Maya; Braw, Yoram; Maoz, Hagai; Levkovitz, Yechiel; Yarnitsky, David; Granovsky, Yelena; Bloch, Yuval (Frontiers in Psychiatry, 2019)
Pain complaints are frequently described by depressed patients, and are mostly attributed to abnormal pain perception and modulation. The present study aimed to assess whether a unique pain processing profile differentiates depressed patients from healthy controls. Participants were 25 patients suffering from a moderate-severe unipolar depressive episode and 25 age and sex-matched healthy controls. Thermal stimuli were used to assess sensory threshold and pain threshold. Pain-60 temperature (temperature that induces pain ratings of 60 out of 100) was the first noxious stimuli to be administered during the experimental session. Central pain inhibition was assessed via conditioned pain modulation (CPM) and the degree of central nervous system excitability was assessed via mechanical temporal summation. Depressed patients reported higher levels of pain compared with healthy controls, and a significantly higher perceived pain during the last month. Additionally, they displayed significantly lower pain-60 temperature values compared with healthy controls (p=.01). Otherwise, no significant group differences were found in measures of pain perception and modulation. Our results suggest that the initial evaluation of pain intensity among depressed patients, as validated by pain-60 temperature values, is increased compared with healthy controls, and might be the mediator between depression and pain complaints. Possibly, depressed patients' negative bias in the processing of pain is similar to their processing pattern of facial expression or future events. Further studies are necessary in order to establish the mechanisms underlying the excessive pain complaints reported by patients with unipolar depression.